2008
DOI: 10.1590/s0102-695x2008000200008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a tomato (Solanum lycopersicum) extract on the labeling of blood constituents with technetium-99m

Abstract: RESUMO: "Efeitos de um extrato de tomate (Solanum lycopersicum) na marcação de constituintes sangüíneos com tecnécio-99m". O tomate (Solanum lycopersicum) é o segundo vegetal mais produzido e consumido no mundo, tendo sido indicado para prevenção e tratamento de câncer, asma e arteriosclerose. Constituintes sangüíneos marcados com radionuclídeos têm sido usados em procedimentos na medicina nuclear. Dados têm mostrado que alimentos e drogas podem alterar a marcação de constituintes sangüíneos com tecnécio-99m (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
7
0
1
Order By: Relevance
“…Technetium-99m radiopharmaceuticals have favorable physical and chemical characteristics 1,2 and widely used in Nuclear Medicine practice 1,3 . Since stannous dichloride (SnCl 2 ) is the most common reducing agent in 99m Tc radiopharmaceuticals preparation, it has been shown that severe biological effects on central nervous system and oral mucosa in animal studies 1,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Technetium-99m radiopharmaceuticals have favorable physical and chemical characteristics 1,2 and widely used in Nuclear Medicine practice 1,3 . Since stannous dichloride (SnCl 2 ) is the most common reducing agent in 99m Tc radiopharmaceuticals preparation, it has been shown that severe biological effects on central nervous system and oral mucosa in animal studies 1,4 .…”
Section: Introductionmentioning
confidence: 99%
“…In Nuclear medicine technetium-99m (99mTc) has been the most utilized radionuclide both in diagnosis nuclear medicine procedures and in basic scientific research (Srivastava, 1987;Early & Sodee, 1999;Saha, 2003;Hladik et al, 1987;Gutfilen et al, 1993;BernardoFilho et al, 1994aBernardoFilho et al, , 1994bAquino et al, 2007;Paoli et al, 2008;Mousinho et al, 2009). This wide use in nuclear medicine is due to its optimal physical characteristics, convenient availability from Mo-99/Tc-99m generator and negligible environmental impact (Hladik et al, 1987;Early et al, 1999;Saha et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…O uso dos produtos naturais nos estudos experimentais tem aumentado consideravelmente no mundo (BernardoFilho et al, 2005;Paoli et al, 2008).…”
Section: Introductionunclassified